Persepsi Mahasiswa Pendidikan Agama Islam Terhadap Efektivitas Pembelajaran Daring pada Masa Pandemi di IAIN Pontianak - Bayu Fitra Prisuna; Ana Rosilawati (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2022)
This study aims to determine the perceptions of Islamic Religious Education students regarding the effectiveness of online learning during the pandemic at IAIN Pontianak. The approach of this research is quantitative research with the type of survey research. The population in this study were all active students of the Islamic Religious Education Study Program in semesters one, three, five & seven with a total of 1164. Sampling used simple random sampling technique and resulted in a research sample of 267 people. The type of instrument used is a student perception questionnaire. Student perceptions of the effectiveness of online learning during the pandemic at IAIN Pontianak were in the